Granulometric fractions and physical-hydric behavior of sandy soils - Santos, Nielton Gonçalo Nunes dos; Olszevski, Nelci; Salviano, Alessandra Monteiro; Cunha, Tony Jarbas Ferreira; Giongo, Vanderlise; Pereira, Janielle Souza (Agrarian, 2019)
Soils attributes such as granulometry and density determine the distribution of pore size and condition physical and differentiated hydraulic behavior. Thus, knowing the characteristics of the soils allow the use of more adequate management techniques that lead to the improvement of the performance of the use of this resource. The aim of this study was to evaluate the diameters of granulometric fractions and the physical-hydric behavior of sandy soils from semiarid region of Brazil. Trenches were excavated to collect, describe, and characterize the morphology of soil samples. The soil bulk density, particle density, granulometry, water retention curve, total porosity and pore size distribution were evaluated. The textural difference among soil studied is expressed with greater emphasis on the amount of macropores, high retention micropores and cryptopores. Fine and very fine sand are the most impacted granulometric fractions increasing macroporosity and reducing high tension microporosity and cryptoporosity. Luvisol with predominance of silt and clay fractions, presents a greater risk of densification and erosion, thus the use of lower irrigation levels is recommended. Acrisols and Luvisol, with predominance of fine and very fine sand fractions, present similar conditions of macroporosity and cryptopores with a low textural gradient. Acrisols and Luvisol do not present major problems regarding the reduction of hydraulic conductivity along the profile. Lower irrigation levels with higher application frequency are suggested due to the low water retention capacity and higher risk nutrients leaching.